Determining the Optimum Processing Parameters of Glass-like Carbon Using Weibull Analysis of its Fracture Behaviour - Oishi, Silvia S. [UNESP]; Botelho, Edson Cocchieri [UNESP]; Paula, Cyntia C.; Rezende, Mirabel C. (Sampe Publishers, 2010)
The probability of failure of glass-like carbon (GC) samples in three-point bend tests was examined using Weibull analysis, and the data correlated with optical microscopy observations. This statistical tool supports a study of GC processing conditions, allowing one to establish the best conditions for manufacturing the material, resulting in the production of material with better uniformity and higher quality. The results show that parameters such as resin viscosity (polyfurfuryl alcohol), centrifugation time, centrifugation velocity and cure temperature of resin, have significant influence on the both pore size and distribution, and consequently on the flexural strength of GC. According to the results, the best processing conditions include using a resin with a viscosity of 3,000 mPa.s, a centrifugation time of 40min, a centrifugation velocity of 3,000 rpm and a cure temperature of 60 degrees C.